2021
DOI: 10.1101/2021.02.18.431915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glioblastoma remodeling of neural circuits in the human brain decreases survival

Abstract: Gliomas synaptically integrate into neural circuits. Prior work has demonstrated bidirectional interactions between neurons and glioma cells, with neuronal activity driving glioma growth and gliomas increasing neuronal excitability. In this study we wanted to know how glioma induced neuronal changes influence neural circuits underlying cognition and whether these interactions influence patient survival. We use intracranial brain recordings during lexical retrieval language tasks in awake humans in addition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 60 publications
1
56
1
Order By: Relevance
“…A growing literature is revealing that gliomas not only disrupt the tissue immediately surrounding the tumour but also exert long-range influences on distant brain areas [ 44 , 45 , 46 ]. Understanding how brain tumours integrate within brain circuits is crucial for prognoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing literature is revealing that gliomas not only disrupt the tissue immediately surrounding the tumour but also exert long-range influences on distant brain areas [ 44 , 45 , 46 ]. Understanding how brain tumours integrate within brain circuits is crucial for prognoses.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, glioblastoma patients present functionally connected voxels within the tumour mass, although with reduced connectivity strength when compared with HCs [ 25 ]. A recent study has found that functionally connected regions within a tumour are enriched for a glioblastoma subpopulation that exhibits a distinct synaptogenic and neurotrophic phenotype [ 46 ]. Although BOLD fMRI has been successfully exploited to quantify tumour oxygenation [ 68 ], microvascular components [ 68 ], tumour delineation [ 20 ] and vascular disruption [ 69 ], interpreting a BOLD signal from tumour and lesioned tissue can be challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to possessing the strongest correspondence to brain connectivity, LCN1 was also enriched with genes involved in neuronal processes such as synaptic signaling and synapse formation. A recent study illustrated that glioma cells enriched with these types of genes integrate into neural circuits involved in lexical processing, and that this neural integration supports tumor proliferation (Krishna et al, 2021). The genomic signature of a glioma may thus be an important predictor of the tumor's eventual migration patterns.…”
Section: Network Spread Of Glioma Tumorsmentioning
confidence: 99%
“…Gliomas are the most common intrinsic brain tumors and a leading cause of neurological impairment in adults. Mounting evidence suggests that malignant gliomas remodel functional neuronal networks, and that these cellular-and network-level interactions impact cognition and survival (1). The mechanistic underpinnings of gliomaneuron interactions and their influence on human cognition is incompletely understood.…”
Section: Main Text Introductionmentioning
confidence: 99%